P243 The association between psychosocial factors and musculoskeletal disorders among nursing home nurses in taiwan. (1st September 2016) - Lin, Ting-Ti; Shiao, Judith Shu-Chu; Hung, Yu-Ju; Guo, Yue-Liang Leon
Abstract : Background: The association between psychosocial factors in workplace and musculoskeletal disorders (MSDs) has been reported among health care workers in hospitals. However, the relationship between psychosocial factors and MSDs among nursing home nurses is relatively lacking. Objective: To determine the association between work-related psychosocial factors and MSDs among nurses in nursing homes. Method: A total of 618 registered nurses from 70 nursing homes hiring more than 10 registered nurses were recruited into the study in 2011. A structured self-administered questionnaire (QN) was used to identify psychosocial hazards in workplace. The QN included Chinese Job Content Questionnaire, a workplace justice scale, and Chinese version of the Copenhagen Burnout Inventory. The Chinese Nordic Musculoskeletal Questionnaire was used to measure the MSDs among study participants. If the score was &x2266;25th percentiles in job control and workplace justice, the "high-risk group for having psychosocial factors" would be categorised. For the group being categorised as "high-risk for having psychological demand and personal burnout", the score was to be &x2267;75th. Multiple logistic regression was used to analyse the association between psychosocial factors and MSDs. Results: A total of 360 eligible questionnaires were included for final analysis. The mean age of registered nurses was 32.7 years and the mean work tenure as a nursing profession was 10.3 years. The most frequent reported MSDs were shoulder (88.3%), neck (81.7%), and low back (74.4%). After adjusting demographic data and ergonomic factors, only personal burnout was associated with neck (AOR = 2.8, 95% CI = 1.3–6.7) and shoulder discomforts (AOR = 2.6, 95% CI = 1.0–7.1). Conclusion: This study showed that personal burnout was related to neck and shoulder disorders among nurses in nursing homes. Preventive strategies to improve nurses' personal burnout are warranted.